Renewable energy (RE) and theory on business sustainability: Malaysia policy development - Kaman Z.K.; Salleh S.F.; Ishak W.W.M. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
Sustainable energy is described as energy that meets the present demand without jeopardizing the needs of future generation. Sustainable development of energy has become the main focus of recent national policies, strategies and development plans of many countries. Renewable energy (RE) is brought to play as it is deemed sustainable and has the potential to thrive in the vastly competitive market of contemporary business. Growing deployment of RE resources in businesses will provide an impetus to accelerate the drive towards clean energy as well as interest and funding for research and development works. In Malaysia, RE was introduced into the energy mix through the Five Fuel Diversification Policy in 2000 and its share has been growing ever since. This article offers a critical analysis of the developing theories linking environmental sustainability to businesses practice, and discusses their implications on Malaysias policy development toward RE. The extensive review presented in this work offers a useful reference for policy makers, corporate managers and researchers who have vested interest in business sustainability and renewable energy related studies. BEIESP.